2010
DOI: 10.1039/c0dt00106f
|View full text |Cite
|
Sign up to set email alerts
|

Selective dimerisation of α-olefins using tungsten-based initiators

Abstract: The selective dimerisation of the alpha-olefins 1-pentene through to 1-nonene is reported using an in situ-generated catalyst derived from tungsten hexachloride, aniline, triethylamine and alkylaluminium halide. The influence of reagent identity and reaction stoichiometry, along with activator, solvent and alpha-olefin substrate choice are probed. The catalyst is found to be highly selective towards dimerisation, minimising the formation of undesired heavier oligomers. Notably, the selectivity within the dimer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 59 publications
3
39
0
Order By: Relevance
“…both tungsten-based dimerization catalyst systems generated in situ and those employing discrete bis(imido) tungsten pre-catalysts, the characteristics of the organoimido ligand have a direct impact on catalytic performance. 24,35,37,38,39 Consequently, the steric and electronic nature of the various imido moieties used in the current study have been assessed and subsequently related to catalytic performance.…”
Section: Steric and Electronic Demands Of The Imido Substituent As Dmentioning
confidence: 99%
See 2 more Smart Citations
“…both tungsten-based dimerization catalyst systems generated in situ and those employing discrete bis(imido) tungsten pre-catalysts, the characteristics of the organoimido ligand have a direct impact on catalytic performance. 24,35,37,38,39 Consequently, the steric and electronic nature of the various imido moieties used in the current study have been assessed and subsequently related to catalytic performance.…”
Section: Steric and Electronic Demands Of The Imido Substituent As Dmentioning
confidence: 99%
“…NEt3, prior to activation with an appropriate alkylaluminum chloride (W:ArNH2:NEt3:Al = 1:2:2:10). 35,36 Thus, these dimerization systems offer scope for tuning product distributions, with not only the nature of the aniline, but also the identity of the alkylaluminum reagent and solvent having been shown to impact significantly on catalytic activity and selectivity. [35][36] While the exact nature of the actual catalytically-active species in these WCl6-derived catalysts is unknown, it has been proposed that tungsten aryl imido (ArN 2-) species are implicated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The in situ generated catalyst although ill-defined remains the most efficient system to promote olefin dimerization. A detailed catalytic study from Sasol led to selectivity above 99 %for dimerization of 1-pentene to 1nonene depending on the catalyst components and their stoichiometry [138). Having a closer look ta the products formed, the authors proposed that the Cossee-Arlman mechanism is effective, supported by a C 2 H 4 /C 2 D 4 co-dimerization experiment leading ta full isotopie scrambling.…”
Section: Vil-tungten Based Catalysts For Selective Ethylene Dimerizationmentioning
confidence: 99%
“…The catalytic ethylene oligomerization performance of the niobium and tantalum complexes 1 to 4 was screened using 15 equivalents of EtAlCl 2 as activator at 60 °C, 40 barg ethylene pressure, and with chlorobenzene as solvent (Table ). The reaction conditions employed here mirror those previously optimised for related industrially‐competitive tungsten imido‐based dimerization systems, thus allowing direct comparison of the performance of the Nb and Ta imido complexes ,,. Utilisation of chlorobenzene as reaction medium for the catalytic testing was adopted since we have previously demonstrated that this was the optimal solvent for ethylene dimerisation mediated by tungsten imido pre‐catalysts and hence its choice facilitates a direct comparison of the performance of the group 5 and 6 catalyst systems; note, catalyst optimisation was not a focus of this current study ,.…”
Section: Resultsmentioning
confidence: 99%